Factors associated with tuberculosis among PLHIV: An observational study in a Government Medical College in West Bengal, India - Saswata Ghosh; Saikat Mandal; Monojit Chakrabarti; Abhijit Dey (Elsevier, 2024)
Background: Tuberculosis (TB) is one of the leading causes of significant morbidity and mortality among the People Living with Human Immune-deficiency Virus (PLHIV) in India. Reducing TB burden among PLHIV is a priority area under the National TB Elimination Program (NTEP). Methodology: We analyzed the routinely collected data from an Anti-Retro-viral Treatment Centre (ARTC) of Malda Medical College, West Bengal with an aim of identifying the factors associated with TB prevalence among the PLHIV. All 739 PLHIV who attended the ARTC during 2020-2022, were included in this study. Results: Mean age of the study participants was 34 years (SD:13). 47.9 % PLHIV received Co-trimoxazole Prophylaxis Treatment (CPT) whereas 67.7 % PLHIV received TB preventive treatment (TPT). Transgender [2.9 (1.4-6)], Males [3.7 (1.8-7.9)], Widow/Separated [2.5 (1.2-5.4)], Living with 2-4 Family members [1.6 (1-2.7)], CD4 count less than 200 [1.9 (1.1-3.2)], those who received CPT [17 (7.1-40.8)] and those who didn't receive TPT [1.6 (1-2.6)] were independently associated with increased risk of developing TB. There was no significant association of Age with TB diagnosis among the PLHIV. Conclusions: It is evident from this study, that introduction of TPT and improving CD4 count by Anti-retroviral Treatment is the key intervention to reduce TB burden among PLHIV. The study found significant association of CPT with TB. Further study may be conducted to determine the actual reason for such association.